Coiled-Coil Motifs of RNA-Binding Proteins: Dynamicity in RNA Regulation - Ford, Lenzie K.; Fioriti, Luana (Frontiers in Cell and Developmental Biology, 2020)
Neuronal granules are biomolecular condensates that concentrate high quantities of RNAs and RNA-related proteins within neurons. These dense packets of information are trafficked from the soma to distal sites rich in polysomes, where local protein synthesis can occur. Movement of neuronal granules to distal sites, and local protein synthesis, play a critical role in synaptic plasticity. The formation of neuronal granules is intriguing; these granules lack a membrane and instead phase separate due to protein and RNA interactions. Low complexity motifs and RNA binding domains are highly prevalent in these proteins. Here, we introduce the role that coiled-coil motifs play in neuronal granule proteins, and investigate the structure-function relationship of coiled-coil proteins in RNA regulation. Interestingly, low complexity domains and coiled-coil motifs are highly dynamic, allowing for increased functional response to environmental influences. Finally, biomolecular condensates have been suggested to drive the formation of toxic, neurodegenerative proteins such as TDP-43 and tau. Here, we review the conversion of coiled-coil motifs to amyloid structures, and speculate a role that neuronal granules play in coiled-coil to amyloid conversions of neurodegenerative proteins.